The search for sam ebook The lost files: the search for sam. - Lore, Pittacus (Lorien Legacies: The Lost Files, 2012)
In this heart-racing 144-page companion novella to the New York Times bestselling I Am Number Four series, discover what happened to Malcolm Goode—the one human on Earth who can help the Garde learn the truth about their past and help them save our planet. No one has seen Sam Goode's father, Malcolm, since he mysteriously disappeared years ago. Sam had always fantasized that he was abducted by aliens. But that was before he knew the truth: aliens do exist, and some of them seek to destroy our world. That was before he himself became another one of their captives. Now father and son are both missing. . . . But when a rogue Mogadorian named Adam, who now has Number One's memories, decides the only way to make up for his past atrocities is to return home and infiltrate the Mogadorian stronghold, he'll find the key to saving both Sam and Malcolm's life.